On analogues of periodic boundary value problems for the Laplace operator in a ball - Sadybekov, Makhmud; Turmetov, Batyrkhan (Eurasian Mathematical Journal, 2012)
We consider a new class of boundary value problems for the Laplace operator in a multi-dimensional ball. These problems are analogues of classical periodic boundary value problems. We prove the correctness of these problems and present a method for constructing all eigenfunctions of the problem.